Biomass characteristics, aeration and oxygen transfer in membrane bioreactors: their interrelations explained by a review of aerobic biological processes - Germain, Eve; Stephenson, Tom (Springer, 2005)
Membrane bioreactor (MBR) is a promising alternative to conventional wastewater treatment methods. However this process is still under-used due to its high running costs. Its main power requirement comes from aeration, which is used to supply dissolved oxygen to the micro-organisms and to maintain the solids in suspension. In addition, in submerged MBRs, aeration is used for membrane cleaning. A complex matrix links the biomass characteristics, the aeration and the oxygen transfer. These parameters can impact on each other and/or delete one another effect. In order to understand the phenomena occurring in MBRs, similar aerobic biological processes, such as fermentation, mineral industry and slurry, were investigated. This review discusses the interrelations of the biomass characteristics (solids concentration, particle size and viscosity), the aeration intensity and the oxygen transfer in MBRs.